Novel Immune Cell Subsets Exhibit Different Associations With Vascular Outcomes in Chronic Kidney Disease Patients—Identifying Potential Biomarkers - Rodríguez-Carrio, Javier; Carrillo-López, Natalia; Ulloa, Catalina; Martín-Carro, Beatriz; Rodríguez-Suárez, Carmen; Naves-Díaz, Manuel; Sánchez-Álvarez, Emilio; Rodríguez-García, Minerva; Arcidiacono, Maria Vittoria; Fernández-Mariño, Belinda; Cannata-Andía, Jorge B.; Suárez, Ana; et al. (Frontiers in Medicine, 2021)
Background: Alterations in novel immune cell subsets, such as angiogenic T-cells (Tang), senescent T-cells (CD4+CD28null) and monocyte subsets are associated to impaired vascular homeostasis in several inflammatory conditions. However, mediators underlying vascular deterioration in chronic kidney disease (CKD) are poorly characterized. This study assessed their role in the vascular deterioration of CKD using a broad spectrum of surrogate markers ranging from altered functionality to overt calcification. Methods: Tang (CD3+CD31+CXCR4+), CD4+CD28null cells and monocytes (CD14/CD16 subsets and ACE expression) were measured in peripheral blood by flow cytometry in 33 CKD patients undergoing peritoneal dialysis (CKD-5PD) and 15 healthy controls (HC). Analyses were replicated in a hemodialysis cohort. Vascular surrogate markers (including adventitial vasa vasorum, pulse wave velocity, intima-media thickness and vascular calcification) were assessed by appropriate imaging methods. Results: In CKD-5PD, decreased Tang levels (p<0.001) were unrelated to clinical features or traditional CV risk factors, but correlated negatively with troponin T levels (r=-0.550, p=0.003). Instead, CD4+CD28null frequency was increased (p<0.001), especially in those with vascular calcifications. Quantitative and qualitative differences were also observed within the monocyte pool, a shift towards CD16+ subsets and ACE expression being found in CKD. Equivalent results were observed in the replication cohort. Each subset associated distinctly with adverse vascular outcomes in univariate and multivariate analyses: while Tang depletion was linked to poor vascular function and subclinical atherosclerosis, increases in CD4+CD28null were associated with overt vascular thickening and calcification. Monocytes were not independently associated with vascular outcomes in CKD patients. Conclusions: Novel T-cell and monocyte subsets are altered in CKD. Altered T-cell subpopulations, but not monocytes, exhibited distinct associations with different vascular outcomes in CKD. Angiogenic T-cells are emerging biomarkers of subclinical vascular deterioration in CKD.